Antimycobacterial activity of fruit of Zanthoxylum acanthopodium DC against Mycobacterium smegmatis - Heddy Julistiono; Fani Gustiani Lestari; Rifki Iryanto; Puspa Dewi Lotulung (Mashhad University of Medical Sciences, 2018)
Objective: Fruits of lemon pepper (Zanthoxylum acanthopodium DC., Rutaceae) have been traditionally used as a spice and in folk medicine for treatment of diarrhea and stomachache. Stomachache could be associated with mycobacterial infection. The present study was designed to investigate the activity of Z. acanthopodium fruits against a non-infectious Mycobacterium smegmatis and to identify the important phytochemical constituent that is toxic towards mycobacteria. Materials and Methods: The broth microdilution method was used to determine the minimal inhibitory concentration (MIC) of ethyl acetate or hexane extract of green, young fruits of Z. acanthopodium. Effect of active extract (hexane) on cell membranee integrity was studied by measuring sodium and potassium leakage into extracelullar liquid using Atomic Absorbtion Spectrophotometer (AAS). Next, cell morphology was observedby using Scanning Microscope Electron (SEM).  Column chromatography was used for fractionation and purification of  hexane extract while the chemical structure of the active compound was determined using NMR technique. Rifampicin, an antimycobacterial compound, was used as positive control. Results: Hexane extract was active against M. smegmatis with an MIC of 64 µg/ml. Plant extract at the concentration of 128 µg/ml caused ions leakage. Concentration of sodium in extracellular liquid of cells treated with plant extract was significantly higher than that of untreated cells. SEM observation revealed cell wall deformation in cultures treated with the extract. NMR spectroscopy analysis of the most active fraction revealed that the compound that exerted toxicity on M. smegmatis was geranyl acetate. Conclusion: Geranyl acetate was an important constituent of Z. acanthopodium fruit that has antimycobacterial activity. Possibly, Z. acanthopodium fruit exert its toxic effects against M. smegmatisthrough damaging cell membrane.